Redefining Activity Tracking Through Older Adults’ Reflections on Meaningful Activities - Wang, Yiwen; Li, Mengying; Kim, Young-Ho; Lee, Bongshin; Danilovich, Margaret; Lazar, Amanda; Conroy, David E; Kacorri, Hernisa; Choe, Eun Kyoung (CHI 2024, 2024)
Activity tracking has the potential to promote active lifestyles among older adults. However, current activity tracking technologies may inadvertently perpetuate ageism by focusing on age-related health risks. Advocating for a personalized approach in activity tracking technology, we sought to understand what activities older adults find meaningful to track and the underlying values of those activities. We conducted a reflective interview study following a 7-day activity journaling with 13 participants. We identified various underlying values motivating participants to track activities they deemed meaningful. These values, whether competing or aligned, shape the desirability of activities. Older adults appreciate low-exertion activities, but they are difficult to track. We discuss how these activities can become central in designing activity tracking systems. Our research offers insights for creating value-driven, personalized activity trackers that resonate more fully with the meaningful activities of older adults.